Parathyroid reimplantation with PR-FaST technique in unselected patients during thyroidectomy. A case series with long term follow up confirming graft vitality and parathormone production. (March 2017) - Cavallaro, Giuseppe; Iorio, Olga; Centanni, Marco; Gargano, Lucilla; Del Duca, Susanna; Gurrado, Angela; Porta, Natale; Petrozza, Vincenzo; Testini, Mario; De Toma, Giorgio
Abstract: Introduction: Parathyroid damage or unintentional excision still affect thyroid surgery and may cause permanent hypoparathyroidism. The only way to recover the excised or ischemic gland functionality is still reimplantation. Many sites of reimplantation have been described, each of one showing both advantages and drawbacks. The aim of this study is to verify results of a new procedure called PR-FaST: Parathyroid Reimplantation in Forearm Subcutaneous Tissue, in a series of unselected patients after long-term follow-up. Materials and methods: From January 2013 to October 2015, 296 consecutive total thyroidectomies have been performed) to treat both benign and malignant thyroid diseases. in 42 cases (14.1%), due to an insufficient blood supply or accidental removal, one parathyroid gland was reimplanted with the PR-FaST technique. Post-operative evaluation was carried out by: total serum calcium (Ca), magnesium (Mg) and phosphorus (P) analysis in the 1st and 2nd postoperative days; Ca, Mg, P and serum iPTH from both arms analysis one week after surgery; Ca and iPTH measurement from both arms 1 months, 3, 6 and 12 months after surgery. Results: We observed transient hypocalcemia requiring calcium replacement therapy in 5 on 42 (11.9%) patients submitted to PR-FaST. No case of permanent hypoparathyroidism was reported. At 1 week after surgery, only 20 patients (47.6%) showed graft vitality, while the number of patients showing graft vitality arised to 33 (79%) after 1 month and to 39 (92.8%) after three and six months. At 1 year 38 (90.5%) patients showed good graft functionality. Considering levels of serum iPTH from both arms, we observed that in case of graft functionality, samples from reimplanted arm revealed in almost all cases values at least 2–3 folds higher than in non reimplanted arm. Conclusions: Results from this prospective evaluation suggest that PR-FaST is a safe and effective procedure, with potential advantages when compared to other techniques of parathyroid reimplantation, that are mainly the possibility to evaluate graft functionality in the follow-up and the easy and well reproducible technique. Furthermore, it can be applied, when needed, to potentially all patients undergoing thyroidectomy. Highlights: Indications to parathyroid reimplantation during thyroidectomy. Follow-up of consecutive patients submitted to parathyroid reimplantation in forearm subcutaneous tissues. Advantages and results of parathyroid reimplantation in forearm subcutaneous tissue.